Connexin 43-Mediated Gap Junction Communication Regulates Ameloblast Differentiation via ERK1/2 Phosphorylation - Yamada, Aya; Yoshizaki, Keigo; Ishikawa, Masaki; Saito, Kan; Chiba, Yuta; Fukumoto, Emiko; Hino, Ryoko; Hoshikawa, Seira; Chiba, Mitsuki; Nakamura, Takashi; Iwamoto, Tsutomu; Fukumoto, Satoshi (Frontiers in Physiology, 2021)
Connexin 43 (Cx43) is an integral membrane protein that forms gap junction channels. These channels mediate intercellular transport and intracellular signaling to regulate organogenesis. The human disease oculodentodigital dysplasia (ODDD) is caused by mutations in Cx43 and is characterized by skeletal, ocular, and dental abnormalities including amelogenesis imperfecta. To clarify the role of Cx43 in amelogenesis, we examined the expression and function of Cx43 in tooth development. Single-cell RNA-seq analysis and immunostaining showed that Cx43 is highly expressed in pre-secretory ameloblasts, differentiated ameloblasts, and odontoblasts. Further, we investigated the pathogenic mechanisms of ODDD by analyzing Cx43-null mice. These mice developed abnormal teeth with multiple dental epithelium layers. The expression of enamel matrix proteins such as ameloblastin (Ambn), which is critical for enamel formation, was significantly reduced in Cx43-null mice. TGF-β1 induces Ambn transcription in dental epithelial cells. The induction of Ambn expression by TGF-β1 depends on the density of the cultured cells. Cell culture at low densities reduces cell–cell contact and reduces the effect of TGF-β1 on Ambn induction. When cell density was high, Ambn expression by TGF-β1 was enhanced. This induction was inhibited by the gap junction inhibitors, oleamide, and 18α-grycyrrhizic acid and was also inhibited in cells expressing Cx43 mutations (R76S and R202H). TGF-β1-mediated phosphorylation and nuclear translocation of ERK1/2, but not Smad2/3, were suppressed by gap junction inhibitors. Cx43 gap junction activity is required for TGF-β1-mediated Runx2 phosphorylation through ERK1/2, which forms complexes with Smad2/3. In addition to its gap junction activity, Cx43 may also function as a Ca2+ channel that regulates slow Ca2+ influx and ERK1/2 phosphorylation. TGF-β1 transiently increases intracellular calcium levels, and the increase in intracellular calcium over a short period was not related to the expression level of Cx43. However, long-term intracellular calcium elevation was enhanced in cells overexpressing Cx43. Our results suggest that Cx43 regulates intercellular communication through gap junction activity by modulating TGF-β1-mediated ERK signaling and enamel formation.